Compostos bioativos, atividade antioxidante e antimicrobiana na casca de cebola roxa (Allium cepa L.) submetidos a diferentes métodos de extração - Viera, Vanessa Bordin (2016)
This study evaluated the use of different methods (focused microwave, ultrasound and conventional agitation) and varying parameters (concentration of solvent, time, temperature, power and pulse) in the extraction of bioactive compounds from red onion skin to obtain an extract with a high content of phenolic compounds, as well as high antioxidant capacity and antibacterial and antifungal activity. The total phenolic content, total flavonoids, anthocyanins, antibacterial capacity and antifungal activity, as well as the in vitro antioxidant capacity, of the extracts were determined by four different methods. The extracts obtained by conventional extraction using agitation had a higher content of total phenolics, flavonoids and total anthocyanins when they were extracted using a higher solvent concentration (80%). With regard to time, it was found that the lowest extraction time of (30 minutes) favored the extraction of compounds with higher antioxidant activity by the DPPH methods and low IC50, and the longest time of (240 minutes) obtained extracts with the highest antioxidant activities using the β-carotene and ABTS methods. The results for focused microwave extraction generally indicated that the highest solvent concentrations (60 to 80%) were more effective in extracting bioactive compounds and, consequently, to obtain extracts with higher antioxidant capacity. Regarding the extraction temperature, it was found that the extracts with highest content of flavonoids and phenolic compounds were obtained at 70 °C. However, the content of total anthocyanins and the DPPH and FRAP methods antioxidant activity of the extracts were not influenced by the extraction temperature. The use of ultrasound to extract bioactive compounds from red onion skin indicated that the extraction of total flavonoids, total anthocyanins and antioxidant activity (FRAP and β-carotene) were efficient at 130 W, with pulsed mode and 60% solvent concentration. The DPPH methods antioxidant activity was only successful at 60% solvent concentration, and the ABTS methods values were highest with 80% solvent, pulsed mode and 130 W power. For the highest inhibiting power of 50% of the DPPH radical (IC50), the best conditions were 130 W, pulsed mode and 40% solvent. The extracts that were obtained through different extraction methods showed no antifungal or antibacterial activity in relation to the different tested microorganisms. However, it can be inferred that red onion skin is a good source of bioactive compounds with antioxidant action and that it can be used as a potential ingredient in the preparation of food products to inhibit lipid oxidation, as well as contributing to reducing agro-industrial waste.